2016
DOI: 10.1177/0363546516652594
|View full text |Cite|
|
Sign up to set email alerts
|

Does Extended Preoperative Rehabilitation Influence Outcomes 2 Years After ACL Reconstruction?

Abstract: Background Rehabilitation before anterior cruciate ligament (ACL) reconstruction (ACLR) is effective at improving postoperative outcomes at least in the short term. Less is known about the effects of preoperative rehabilitation on functional outcomes and return-to-sport (RTS) rates 2 years after reconstruction. Purpose/Hypothesis The purpose of this study was to compare functional outcomes 2 years after ACLR in a cohort that underwent additional preoperative rehabilitation, including progressive strengthenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 31 publications
2
103
1
5
Order By: Relevance
“…While the case study athlete had co-morbidities and other factors that complicated her rehabilitation process, her 22-month outcomes compared favorably to recently published data from large cohorts. 14 It is likely that athletes with isolated ACL injuries could initiate the early on-ice phase sooner (i.e., ≥16 weeks versus 7 months post-operatively) and complete the entire program earlier. Nevertheless, even for the uncomplicated athlete, we recommend not initiating the return-to-sport phase until at least 9 months post-operatively due to increased risk of re-injury for returning to sport before this time-frame, even in the absence of impairments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the case study athlete had co-morbidities and other factors that complicated her rehabilitation process, her 22-month outcomes compared favorably to recently published data from large cohorts. 14 It is likely that athletes with isolated ACL injuries could initiate the early on-ice phase sooner (i.e., ≥16 weeks versus 7 months post-operatively) and complete the entire program earlier. Nevertheless, even for the uncomplicated athlete, we recommend not initiating the return-to-sport phase until at least 9 months post-operatively due to increased risk of re-injury for returning to sport before this time-frame, even in the absence of impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Her Knee Injury and Osteoarthritis Outcome Score 45 subscale scores are similar to or higher than Delaware-Oslo ACL Cohort and Multicenter Orthopaedic Outcomes Network (MOON) scores among subjects two years after ACLR. 14 …”
Section: Case Description and Applicationmentioning
confidence: 99%
“…Physiotherapists consider pre-operative rehabilitation to have an important influence on post-operative outcomes (Ebert, Webster, Edwards, Joss, D'Alessandro, et al, 2018). A structured physiotherapy-led pre-ACLR rehabilitation programme of up to 27 sessions has been shown to be effective and safe, and to improve outcomes two years after ACLR (Alshewaier, Yeowell, & Fatoye, 2017;Eitzen et al, 2010;Eitzen et al, 2009;Failla et al, 2016;Logerstedt et al, 2013). Our research found that 24% of people did not receive physiotherapy treatment prior to ACLR, which suggests the post-operative outcomes for almost a quarter of people in our sample may have been sub-optimal.…”
Section: Duration and Quantity Of Physiotherapy Treatmentmentioning
confidence: 99%
“…A structured pre-operative physical rehabilitation programme produces better post-operative functional outcomes (Eitzen, Risberg, & Holm, 2009;Failla et al, 2016;Logerstedt, Lynch, Axe, & Snyder-Mackler, 2013). Supervised physiotherapy is routinely prescribed following ACL surgery (Han, Banerjee, Shen, & Krishna, 2015), and supervised rehabilitation can be associated with better outcomes than unsupervised (Christensen, Miller, Burns, & West, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additional pre-operative rehabilitation and consequently post-operative rehabilitation significantly improves the patient's functional outcome of ACL reconstruction (12).…”
Section: -Extensor Mechanism Dysfunctionmentioning
confidence: 99%